Mine, ours or yours? Unintended framing effects in dictator games - Andreas Bergh; Philipp C. Wichardt (Research Institute of Industrial Economics (IFN), 2018)
This paper reports results from a classroom dictator game comparing the effects of three different sets of standard instructions. As was shown by Oxoby and Spraggon (2008), inducing a feeling of entitlement - one subject earning the endowment - strongly affects allocations in dictator games towards the owner of the money (both dictator and receiver). The present results show that seemingly small differences in instructions induce fundamentally different perceptions regarding entitlement. Behavior is affected accordingly, i.e. instructions inducing subjects to perceive the task as distributive rather than a task of generosity lead to higher allocations to receivers (average 52% vs. 35%). A theoretical explanation integrating monetary as well as social incentives and emphasizing potential effects of uncertainty about the latter is discussed (cf. Bergh and Wichardt, 2018).
Keywords: C70; C91; D63; 330; Dictator games; Framing effects; Property rights; Social preferences